The impact of high intensity training and sports on recipients of solid organ transplants: a narrative review - Kayeye, A.; Triantafyllou, I.; Mathur, S.; Janaudis-Ferreira, T. (Frontiers in Sports and Active Living, 2024)
Objectives: High intensity exercise in individuals post solid organ transplant (SOT) remains a largely understudied phenomenon with potential r i s k s a n d benefits. additonally, the optimal training protocols are still unclear. This narrative review aimed to explore the impact of high-intensity exercise training, and strenuous sports on solid organ transplant recipients (SOTRs).Methods: We conducted a narrative review of intervention studies of any design that included high-intensity exercise training, cross-sectional studies of strenuous sports and activities, and individual reports documenting post-SOT performance at highly competitive or physiological levels. We used MEDLINE to search for relevant articles followed by a manual search for additional articles. Data were extracted and results were summarized.Results: High intensity and strenuous exercise appear to be safe among stable SOTRs. High intensity protocols consistently demonstrated improvement in VO2peak, and reduction in coronary artery disease prevalence with inconsistent findings in body composition, health related quality of life outcomes, and cardiovascular biomarkers. Pre-transplant athletes showcase notable achievements and physiological adaptations post-transplantation, highlighting the capacity for athletic performance among this population. However, caution is warranted in interpreting the findings from these studies due to limitations in generalizability and other methodological limitations.Conclusion: As evidenced by current literature, high intensity exercise emerges as a promising exercise method for safely improving various physiological parameters, and reducing the prevalence of coronary heart disease in SOTRs. It can induce similar or greater effects to moderate intensity exercise however, follow-up studies indicate low retention. Further research of higher methodological rigor is warranted in this field to advance understanding, and to guide evidence-based practice.